Assessment of Nurses- midwives’ Knowledge of Nursing Measures for the Use of Utero-tonic Drugs in Al_Kut city hospitals - Huda Abdulkadhim Thamer, Aqeel Habeeb Jasim (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To assess nurses- midwives’ knowledge about nursing measures related to Utero-tonic Drugs Use . Method: A descriptive design study was conducted from 1st May 2021to 10th March 2022 in two hospitals at al- kut city on nurses and midwives who work at maternity hospitals. Non- probability (Convenience sampling) was used to collect the data from select 60 nurses and midwives. A questionnaire is an instrument to collect the demographic, occupational information and knowledge which consists of 40 items. Validity of content was determined through reviewing it by (13) experts and reliability of tools was determined through a pilot study. descriptive statistics were used to analyze the data. Results: the result of the study showed that more than half of study sample were within age group (20-24) years The results of study indicated that assessment of nurses – midwives’ knowledge were in adequate (60%) and adequate (40%) about nursing measures related to uterotonic drugs use. The study findings showed that nurse midwives have in adequate knowledge regarding nursing measures of uterotonic drugs use. Establish training courses concerning right methods of nursing measures for use uterotonic drugs for all nurses and midwives who work at maternity hospitals in al-kut city. Conclusions: The study showed that assessment of nurses-midwives’ knowledge about nursing measures of uterotonic drugs use were inadequate level and these have effect on pregnant women and their fetus.